Le regard impossible - Mathias Kusnierz (Transatlantica)
This paper discusses the issues of photorealistic illusion and ideological production in American blockbusters through an analysis of their digital effects and computer generated images (CGI). I adopt a Marxist perspective to question their discourse. Attention is first paid to the historical, theoretical and technical conditions of the photorealism of digital effects and CGI. I then examine how films use photorealism to ensure the audience’s adherence to the ideology of the American way of life. I show that the mechanisms of ideological production at play in digital effects and CGI form a system that aims first and foremost to conceal their discursive nature, then obliterate the contradictions of reality in order to assign a specific viewing position for the audience within the symbolic and political order.